A fault tolerant service discovery by self-organisation: a MAS approach. (1st January 2013) - Mellah, Hakima; Hassas, Salima; Drias, Habiba
The service discovery has become an emerging phenomena in software engineering and process engineering as well. The paper presents a multi agent system (MAS) approach, for service discovery process, based on a self-organising protocol. This feature is very crucial for assuring a correct service delivery, to avoid failures or mal-function for the service discovery environment. The requirement for self-organising choreographed services have been well realised, in case of operational, functional and behavioural faults. The self-organising protocol is conceived from bacteria colony.